Yield Gap-Based Poverty Gaps in Rural Sub-Saharan Africa. (March 2015) - Dzanku, Fred M.; Jirström, Magnus; Marstorp, Håkan
Summary: Given Africa's challenge of feeding a growing population, narrowing yield gaps is an efficient way of raising production under covariate constraints. Using household panel data from 21 regions in eight sub-Saharan African countries, this article unravels the determinants of yield gaps. It also tests the hypothesis that poverty gaps are increasing with yield gaps. The results suggest that yield gaps are increasing with cultivated area; that yield differences are reducing with fertilizer use, particularly when combined with improved seeds in low production potential regions; that poverty gaps are increasing with yield gaps, particularly in low production potential regions.